Isolated aortic root dilation in homocystinuria. Issue 1 (4th October 2017) - Lorenzini, Massimiliano; Guha, Nishan; Davison, James E.; Pitcher, Alex; Pandya, Bejal; Kemp, Helena; Lachmann, Robin; Elliott, Perry M.; Murphy, Elaine
Abstract: Background: Vascular complications in homocystinuria have been known for many years, but there have been no reports to date on involvement of the ascending aorta. Methods: We conducted a cross‐sectional study of patients with homocystinuria, known to a single metabolic centre, and evaluated in 2016 with a transthoracic echocardiogram. Aortic root dilation was defined as Z‐score ≥ 2.0 SD, and graded mild (Z‐score 2.0–3.0), moderate (Z‐score 3.01–4.0) and severe (Z‐score > 4.0). Results: The study population included 34 patients, median age of 44.3 years (IQR 33.3–52.2), 50% males, 69% diagnosed aged <18 years and 29% pyridoxine‐responsive. Eight (24%) had a history of hypertension. Seven patients (21%) were found to have a dilation of the aortic root, mild in two cases (6%), moderate in four (12%) and severe in one (3%). None had dilation of the ascending aorta. Significant aortic regurgitation, secondary to moderate aortic root dilation, was documented in two patients. A single patient had significant mitral regurgitation due to prolapse of both valve leaflets, as well as mild aortic root dilation. Comparing patients with a dilation of the aortic root to those without, there were no significant clinical, laboratory or echocardiographic differences, with the only exception being that the diameter of the ascending aorta was larger in the group with a dilated aortic root, albeit within normal limits. Conclusions: A subset of patients with homocystinuria have isolated dilation of the aortic root similar to that observed in Marfan syndrome.